Characterization of Protein-Facilitated Ion-Transfer Mechanism at a Polarized Aqueous/Organic Interface - Arooj, Mahreen; Arrigan, Damien; Mancera, Ricardo (AMER CHEMICAL SOC, 2019)
© 2019 American Chemical Society.